Axel Honneth and the neo-Idealist turn in critical theory. (October 2014) - Thompson, Michael J.
I provide a critique of Axel Honneth's theory of recognition by calling into question the extent to which recognitive relations are immune to the effects of social and economic power and their ability to shape consciousness and moral cognition. I maintain that as a theory of socialization, Honneth's theory is inadequate to deal with the strong structural-functional forces that hold administrative-capitalist societies together. This has the effect of constituting subjectivity in particular ways, and this problem of the constitution of the personality and consciousness of individuals vitiates the descriptive and normative claims of the theory of recognition. I end by considering an alternative way to view recognition and its role in promoting a form of critical subjectivity.